Critical Reception of Patrick White’s Fiction in Czechoslovakia - KUŠNÍR, Jaroslav (Anafora, 2023)
This paper deals with the critical reception of Australian writer Patrick White’s fiction in Czechoslovakia, and provides an analysis of both the socio-historical context related to the publication of and the critical response to White’s fiction in Czechoslovakia as manifested in the essays (afterwords to the translations) and select reviews of his work. The article emphasizes the specificity of the critical reception of White’s fiction in Czechoslovakia, especially due to the critics’ objective and non-ideological treatment of his work, as well as the loss of interest in White’s fiction by both the publishers and the critics in the period after 1989.